2010
DOI: 10.1177/0011000009358459
|View full text |Cite
|
Sign up to set email alerts
|

Belongingness as a Protective Factor Against Loneliness and Potential Depression in a Multicultural Middle School

Abstract: This study examines belongingness as a strengths-based protective factor. Belongingness is investigated in relationship to the threat of low peer acceptance for loneliness and of high loneliness for depression in adolescents. Data were collected from peers for adolescents’ peer acceptance and from adolescents themselves for other variables. Ratings of peers and self-reported survey data were analyzed together from data collected from 294 eighth-grade students from a culturally and ethnically diverse school. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 54 publications
8
52
1
1
Order By: Relevance
“…Girls believed that leaving the group would mean that they did not belong anywhere. Baskin et al (2010) wrote of the importance of 'belongingness' in peer cliques for adolescents, naming it as a key factor in their well being; however, it would appear that for vulnerable girls 'belongingness' may well come at a price. For these girls, belonging to a dysfunctional group was better than not belonging to a group at all.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Girls believed that leaving the group would mean that they did not belong anywhere. Baskin et al (2010) wrote of the importance of 'belongingness' in peer cliques for adolescents, naming it as a key factor in their well being; however, it would appear that for vulnerable girls 'belongingness' may well come at a price. For these girls, belonging to a dysfunctional group was better than not belonging to a group at all.…”
Section: Discussionmentioning
confidence: 99%
“…The early years of adolescence (10 -15 years) are marked by rapid cognitive, physical, emotional and social development (Frydenberg, Care, Freeman, & Chan, 2009) with friendships becoming even more important to their social networks (Collins & Laursen, 2004). Baskin, Wampold, Quintana, and Enright (2010) named belongingness, associated with friendships, as a key factor in the emotional well-being of adolescents as it offered potential protection against the harmful effects of low self-esteem and depression. The many benefits of friendships have been well documented and they include allowing adolescents to explore a range of issues that might be regarded as personal along with the opportunity to discuss conflicting reasoning and judgements (for a summary, see Berk, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There is strong evidence that loneliness is related to anxiety [26][27][28] and depression [29][30][31], but few studies have reported associations between loneliness and somatic symptoms [1]. Loneliness among children and adolescents has been studied mainly in the school setting, and few researchers have tested initiatives to buffer feelings of loneliness [32][33][34]. Furthermore, as far as we are aware, no studies have reported on relational trust as a potential to reduce harmful effects of loneliness in school.…”
Section: Introductionmentioning
confidence: 99%
“…In a study, as in [33] it was reported that loneliness predicted depressive symptoms. Reference [34] had also found out that loneliness predicted depression. Regression analysis demonstrated that depression was predicted by loneliness scores.…”
Section: Introductionmentioning
confidence: 99%